Revitalisation of urban public space in core zone, George Town world heritage site, Pulau Pinang / Maimunah Ramlee - Ramlee, Maimunah (2017)
Revitalisation of urban public space is a process to redevelop the public space area in line with the population and development growth. It is essential for urban revitalisation in meeting the users' needs in urban public space to create a successful public space. This research looks at the factors related to a revitalisation of urban public space in George Town Pulau Pinang. The research is to identify the features of public space which could usefully be undertaken for revitalisation purposes and how to make the public space more functional with positive impact on modern urban life. This research is based on data obtained from in-depth interviews, observation and questionnaire survey regarding public space successful factors based on the local residents' and tourists' assessment. The data were analysed to evaluate and determine the public space attributes and its level of preferences that influence the alternative ways to the revitalisation of urban public space in terms of planning and management of successful urban public space. Finally, the recommendations of this research should be able to revitalise urban public space particularly in terms of the physical qualities, functionality and suitability, users' preferences, needs and comfort at public space. This recommendation is expected to assist the local authority to successfully managing urban public space. Therefore, with this recommendation can contribute to the improvement of urban public space planning and management in George Town.